A 33 hour period for the Wolf-Rayet/black hole X-ray binary candidate NGC 300 X-1 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Context. NGC 300 X-1 is the second extragalactic candidate, after IC 10 X-1, in the rare class of Wolf-Rayet/compact object X-ray binary systems exemplified in the Galaxy by Cyg X-3. From a theoretical point of view, accretion onto a black hole in a detached system is possible for large orbital periods only if the mass of the relativistic object is high or the velocity of the accreted wind is low.Aims. We analysed a 2 week SWIFT XRT light curve of NGC 300 X-1 and searched for periodicities. Methods. Period searches were made using Lomb-Scargle periodogram analysis. We evaluated the confidence level using Monte Carlo simulations.Results. A period of 32.8 +/- 0.4 h (3 sigma error) was found for NGC 300 X-1 with a confidence level > 99%. Furthermore, we confirm the high irregular variability during the high flux level, as already observed in the XMM-Newton observations of the source. A folded XMM-Newton light curve is shown, with a profile that is in agreement with SWIFT. The mean absorbed X-ray luminosity in the SWIFT observations was 1.5 x 10(38) erg s(-1), close to the value derived from the XMM-Newton data.Conclusions. While Cyg X-3 has a short period of 4.8 h, the period of NGC 300 X-1 is very close to that of IC 10 X-1 (34.8 +/- 0.9 h). These are likely orbital periods. Possibility of formation of accretion disk for such high orbital periods strongly depends on the terminal velocity of the Wolf-Rayet star wind and black-hole mass. While low masses are possible for wind velocities <= 1000 km s(-1), these increase to several tens of solar masses for velocities > 1600 km s(-1) and no accretion disk may form for terminal velocities larger than 1900 km s(-1).
Keywords: X-rays : individuals : NGC 300 X-1; X-rays : binaries; stars : Wolf-Rayet